Efficient Concurrent Analysis of Mesotrione, Atrazine, Benoxacor and S-Metolachlor in Herbicide Formulate: Developing and Validating a Reversed-Phased HPLC Method - Anum Hafeez; Sajid Iqbal; Iffat Abdul Tawab Khan; Qurrat-ul-Ain (Pakistan Journal of Analytical & Environmental Chemistry, 2025)
An effective, simple and reliable simultaneous determination method for four active compounds, mesotrione, benoxacor, atrazine and S-metolachlor, in herbicide formulate was first-time developed and substantiated in current study using reversed-phased high performance liquid chromatography, following ICH guidelines. The chromatographic separation with fine resolution was conducted on a 5 μm C-18 column (L x id, 15 cm x 4.6 mm) using acetonitrile:water 70:30 (v/v) at 1.0 mL/min flow rate and wavelength 260 nm (UV detector). The retention times for mesotrione, atrazine, benoxacor and S-metolachlor were obtained as 1.90, 3.50, 3.95, and 5.10 min, respectively. Limits of detection of mesotrione, atrazine, benoxacor and S-metolachlor were found to be 2.57, 2.27, 1.28, and 1.32 µg/mL, whereas limits of quantitation were 7.80, 6.86, 3.86, and 4.01 µg/mL, respectively. The regression coefficients from calibration curves were ˃ 0.998 for all studied pesticides. The method reproducibility was evaluated as intra-day precision (0.85–1.52 %RSD) and inter-day precision (0.67–1.81 %RSD). The method accuracy was estimated through inter-laboratory comparison among three laboratories. The developed method is quite rapid, inexpensive, robust, precise, accurate, linear and sensitive for the purpose of quality control check of mesotrione, atrazine, benoxacor and S-metolachlor simultaneously in herbicide formulations.